VD_FINDINFO Décision / 2011 / 801 vom 14. Dezember 2010 - VD Tribunal cantonal (2010)
SUSPENSION DANS LA PROFESSION, MESURE DISCIPLINAIRE | 12 let. a LLCA, 12 let. c LLCA, 12 let. h LLCA, 12 let. i LLCA